Effect of Ramadan Fasting on Total cholesterol (TC) Low density lipoprotein cholesterol (LDL-C) and High density lipoprotein cholesterol (HDL-C) in Healthy Adult Male - Ara, Tanzin; Jahan, Nasim; Sultana, Nayma; Choudhury, Rama; Yeasmin, Tahmina (Journal of Bangladesh Society of Physiologist, 2016)
Background: Ramadan fasting has some effects on anthropometric, metabolic and physiological functions in the healthy subjects. Objective: To observe the effects of Ramadan fasting on serum total cholesterol (TC) low density lipoprotein cholesterol (LDL-C) and high density lipoprotein cholesterol(HDL-C) in healthy adult male. Methods: This prospective observational study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka between January and December 2013. Sixty healthy adult male aged 24 to 28 years were studied. Serum TC, LDL-C and HDL-C levels were estimated by enzyme method. Data were collected twice; 1-3 days before Ramadan fasting (BRF) and then during 25th -27th days of Ramadan fasting (ARF) and compared. The statistical analysis was done by paired sample t test. Results: In this study, the mean body weight (BW), BMI, TC, LDL-C levels were significantly (p<0.001) decreased, and HDL-C level was significantly (p<0.001) increased in ARF than BRF. Conclusion: The results of this study revealed that Ramadan fasting has some beneficial effects on cholesterol and lipoprotein status in healthy adult male. Bangladesh Soc Physiol. 2015, December; 10(2): 46-50